Analysis the Effect Legal Audit, Control and Supervision on The Optimization of Fixed Asset Management (Land and Buildings) In the Regional Government of Papua Province - Siti Hasanah; Entar Sutisman; Sahrul Ponto (West Science Social and Humanities Studies, 2023)
The purpose of this study is to empirically examine the effect of legal audit, supervision, and control on the optimization of fixed asset management in the Papua Provincial Government. The method used in this study is a quantitative method of causality to evaluate the relationship between the independent variable and the dependent variable. The results showed that Legal audit and supervision have a significant effect on optimizing the management of fixed assets of land and buildings as well as on the local government of Papua Province, showing that clear status and good supervision can improve the management of fixed assets.